2019
DOI: 10.1002/adfm.201905816
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric‐Polymer‐Enabled Contactless Electric Power Generation in Triboelectric Nanogenerators

Abstract: Triboelectric nanogenerators (TENGs) are considered as one of the most important renewable power sources for mobile electronic devices and various sensors in the Internet of Things era. However, their performance should inherently be degraded by the wearing of contact surfaces after long‐term use. Here, a ferroelectric polymer is shown to enable TENGs to generate considerable electricity without contact. Ferroelectric‐polymer‐embedded TENG (FE‐TENG) consists of indium tin oxide (ITO) electrodes, a polydimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The performance of a TENG device is very different depending on whether a positive or negative voltage is applied for poling (Figure 2), regardless of the polymer used. This phenomenon of one polarization direction resulting in a larger impact than the other is widely reported before (Bai et al, 2014;Suo et al, 2016;Lee et al, 2016;Sutka et al, 2018;Lap cinskis et al, 2019;Kim et al, 2019;Huang et al, 2020); however, the explanation provided for that has been inaccurate. We argue that the observed difference can be explained by elementary match and mismatch between the directions of the electric field from the ferroelectric dipole moment and the dipole moment created by triboelectric charges.…”
Section: Ll Open Access Isciencementioning
confidence: 59%
See 1 more Smart Citation
“…The performance of a TENG device is very different depending on whether a positive or negative voltage is applied for poling (Figure 2), regardless of the polymer used. This phenomenon of one polarization direction resulting in a larger impact than the other is widely reported before (Bai et al, 2014;Suo et al, 2016;Lee et al, 2016;Sutka et al, 2018;Lap cinskis et al, 2019;Kim et al, 2019;Huang et al, 2020); however, the explanation provided for that has been inaccurate. We argue that the observed difference can be explained by elementary match and mismatch between the directions of the electric field from the ferroelectric dipole moment and the dipole moment created by triboelectric charges.…”
Section: Ll Open Access Isciencementioning
confidence: 59%
“…Another possibility is the modification of surface or physicochemical properties of the triboelectric material Lap cinskis et al, 2019;Fan et al, 2014;Yun et al, 2015;Wang et al, 2016). The performance can be also enhanced by using ferroelectric polymer or composite films as the contacting surfaces (Bai et al, 2014;Seung et al, 2017;Suo et al, 2016;Chun et al, 2015;Yang and Daoud, 2017;Choi et al, 2017;Lee et al, 2016;Sutka et al, 2018;Lap cinskis et al, 2019;Kim et al, 2019;Huang et al, 2020). State-of-the-art performance of ferroelectric material-based TENG devices can be expected when the ferroelectric material layers on contacting sides of the device are inversely polarized ( Sutka et al, 2018;Lap cinskis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, can light LEDs without charge storage (see Figure 8e). Kim et al [208] have reported a much simpler way to enhance TENG durability, by employing the concept of reduced contact number cycles in ferroelectric, PVD-based TENG, with ITO as the electrode and PDMS as an elastomer. They showed that the up-sided polarization (58 pm/V) of PVDF led to extremely fast charge accumulation and larger TE-outputs, when compared with a downside (36 pm/V) and non-polarized (1.1 pm/V) PVDF under contact state.…”
Section: Device Design and Output Power Optimization In Triboelectric Nanogenerators Tengmentioning
confidence: 99%
“…Ferroelectric polymers are functional materials that possess spontaneous polarization that is switchable with an electric field [ 10 , 11 ]. This functionality has encouraged research directed to the use of ferroelectric polymers as active materials in sensors [ 12 ], non-volatile memory [ 9 , 13 ], and nanogenerators for energy harvesting [ 14 , 15 ]. Ferroelectric polymers have also been studied in combination with semiconducting polymers for potential applications such as low-voltage organic diodes [ 16 ], non-volatile memory [ 17 , 18 ], and organic solar cells [ 1 ].…”
Section: Introductionmentioning
confidence: 99%